2020
DOI: 10.29309/tpmj/2020.27.09.4107
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron sucrose in malnourished children with iron deficiency anemia.

Abstract: Objectives: To compare the mean hemoglobin level before and six weeks after giving intravenous iron sucrose therapy in malnourished children having iron deficiency anemia. Study Design: Quasi Experimental Study. Setting: Nutritional Stabilization Centre, Children Hospital and Institute of Child Health, Multan. Period: From July 2018 to December 2018. Material & Methods: A total of 80 patients were enrolled in the study. Hemoglobin level at baseline was recorded. IV iron sucrose therapy was divided into 3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…documented. A rise in posttreatment hemoglobin levels implies that erythropoietic recovery is achieved with intravenous iron sucrose which also 16,18 strengthens the findings of our study. The most common side effect in our study is fever 10% whereas the study by Mantadakis et al reported the most common adverse effect of parental iron to be injection site extravasation followed by a 19 transient alteration in taste.…”
Section: Table II :Feeding History and Diagnosis At The Time Of Admis...supporting
confidence: 87%
“…documented. A rise in posttreatment hemoglobin levels implies that erythropoietic recovery is achieved with intravenous iron sucrose which also 16,18 strengthens the findings of our study. The most common side effect in our study is fever 10% whereas the study by Mantadakis et al reported the most common adverse effect of parental iron to be injection site extravasation followed by a 19 transient alteration in taste.…”
Section: Table II :Feeding History and Diagnosis At The Time Of Admis...supporting
confidence: 87%
“…Similarly, our study outcomes find resonance with a study recently conducted in Multan, reporting a statistically significant increase in mean Hb levels after six weeks of active supplementation 11 . Another national study documented that parenteral iron sucrose therapy improved mean Hb levels in malnourished children with IDA 12 . Meanwhile, another Pakistani study reported Hb levels rising to 9.21±1.13 g/dL with IV iron sucrose therapy 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study in Pakistan sets itself apart from most others. Instead of focusing solely on malnourished children, as many studies have done before 11,12 , we are taking a broader approach. We're including children with iron deficiency anemia, no matter their nutritional status.…”
Section: Introductionmentioning
confidence: 99%